Microbial hazard analysis and control of the fastfood preparation and retail-vending of spaghetti - Jose, Zierlyn Formantes; Azanza, Ma. Patricia V. (2000.)
ABSTRACT this study established the microbial hazards associated with the preparation and retail-vending of ready-to-eat spaghetti from a small-scale fastfood establishment. The study ws conducted under the University of the Philippines Office of the Research Coordination (UP-ORC) research project No. 09808-Ns entitled "Applications of the Hazard Analysis Critical Control Point (HACCP) System to Small-scale Fastfood Establishments." The major processes in the foodflow diagram of spaghetti included: cooking of sauce at the commissary,cooking noodles in the food stall within the foodcourt, hot-holding of sauce, hold-on display of noodles, and mixing of noodles and sauce prior to serving. The initial microbial load of raw ground beef, thawing of frozen beef, cooking of sauce,hot-holding of sauce, and hold-on display of cooked noodles at ambient conditions were identified as critical control point (CCP) in the foodflow. The main sources of microbial contamination identified were the initial microbial uality of raw ground beef, food contact surfaces, and food handlers. Overnight thawing at room temperature, relatively low temperature attained during cooking of sauce, hot-holding of sauce, and the ambient hold-on conditions of cooked noodles during the retail-vending operations provided conducive for microbial growth and surivival. The microbial flora of the mixed spaghetti during the 0-6 h vending operation was established: 〖10〗^3-〖10〗^6 cfu/g; coliform count of <10-〖10〗^4 MPN/g; and 〖10〗^2-〖10〗^3 cfu/g Staphyloloccus count. The presence of Salmonella per 25g sample was detected in 1 of the 3 trials. Recommendations of the study included purchasing of high quality raw ingredients particularly ground beef, use of better thawing procedure, practice of good manufacturing practices, and adaptation of cook-chill-reheat-serve operation.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Pasta -- Microbial analysis; Food preparation -- Safety measures